Factors influencing the development of practical skills of interns working in regional hospitals of the Western Cape province of South Africa - Joerg Jaschinski; Marietjie R. de Villiers (South African Family Practice)
Background: Clinical skills and the ability to perform procedures is a vital part of general medicine. Teaching these skills to aspiring doctors is a complex task. It starts with a good theoretical preparation and some practical experience at university. On graduating from university, each doctor is faced with the task of transforming theoretical knowledge into the practical, procedural skills of a competent professional. This study aims to assess the perceptions of intern doctors working in regional hospitals in the Western Cape of their skills training both at undergraduate level and during the intern year.